Modeling the stay plan and discent success: a proposal for mapping the evasion context (Research, Society and Development, 2021)
The study presents a proposal for the modeling and mapping of academic processes, supporting the prevention and identification of the causes of student dropout, in order to support the objectives of the permanence and success plan (PPE) developed by some educational institutions. The proposal was elaborated through meetings with all agents present in the target institution of the research, namely: Management team, Faculty, Administrative Technicians in Education, Outsourced Persons and Students. Thus, the work aims to identify the moment when the student starts a context of possible dropout. The meetings were duly registered in the institutional information systems and, in turn, enabled the elaboration, analysis and validation of the process mapping, with the identification of the exact moment when the student starts a possible context of evasion or retention, but it was also revealed a short salutary and preventive time interval that demands specific actions to avoid the consolidation of dropouts. Furthermore, the theme is still motivated by the General Law for the Protection of Personal Data (LGPD), given the existence of sensitive data of students and the processing of the respective processes by various institutional sectors, which demands greater attention from educational institutions for the management of its internal processes.